EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN AUDIOVISUAL DALAM MENINGKATKAN PEMAHAMAN MATERI DI KALANGAN SISWA SEKOLAH DASAR - Sari, Yunita; Puspita, Fitri Dewi; Yatin Mulyono (Jurnal Metabio, 2025)
This study aims to determine the effectiveness of using audiovisual learning media in improving material comprehension among elementary school students through a meta-analysis approach. A quantitative method was employed by systematically selecting relevant experimental articles from national and international databases. Inclusion criteria included experimental design, elementary-level subjects, and availability of statistical data such as means, standard deviations, and sample sizes. Seven eligible articles were analyzed using Cohen’s d formula to measure effect size, followed by descriptive and inferential analysis. The results showed an average effect size of 1.46, which is classified as a large effect. This indicates that audiovisual media significantly enhance students’ material comprehension. These findings support the importance of using audiovisual-based learning media as an effective and applicable strategy in elementary school instruction. The study also revealed variations across studies influenced by intervention duration, subject matter, and the quality of media implementation.